Chemo-mechanical degradation in V2O5 thin film cathodes of Li-ion batteries during electrochemical cycling. Issue 41 (15th July 2019) - Zhang, Yuwei; Luo, Yuting; Fincher, Cole; Banerjee, Sarbajit; Pharr, Matt
Abstract : We have devised an approach to fabricate dense textured V2 O5 thin films, which allows us to scrutinize the root cause of capacity fade in V2 O5 cathodes of Li-ion batteries. Abstract : We have devised an approach to fabricate dense textured V2 O5 thin films, which allows us to scrutinize the root cause of capacity fade in V2 O5 cathodes of Li-ion batteries. Specifically, we performed in situ measurements of stress of V2 O5 thin films during 50 electrochemical cycles. Surprisingly, electrochemical cycling appears to induce elastic and rate-independent deformation over a voltage range relevant to battery operation (4–2.8 V). However, the compressive stresses gradually increase with cycle number during the first few cycles, likely due to side reactions and/or residual Li left in the V2 O5, even after delithiation (to 4 V). Further cycling leads to accumulated mechanical damage ( e.g., fracture, delamination) and structural damage ( e.g., amorphization), which ultimately result in severe capacity fade.